PENTINGNYA ETIKA KOMUNIKASI DI ERA SIBER - Desak Made Sueni; I Nyoman Buda Asmara Putra (Maha Widya Duta : Jurnal Penerangan Agama, Pariwisata Budaya, dan Ilmu Komunikasi, 2022)
The development of communication technology with its various new media platforms forms a new society called cyber society. The massive digital content consumed by the cyber community results in frequent miscommunication and disharmony due to a lack of responsibility and communication ethics. This research is a qualitative research using literature study. Based on the results of this study, ethics has a very vital role in communication in the cyber era. We must implement internet ethics in cyber society, starting with ourselves, family and those closest to us, learning to use the internet safely and responsibly. This is very important to prevent violations of the law contained in Law Number 19 of 2016 amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions. Imprisonment sentences accompanied by fines of hundreds of millions to billions of rupiah await if they violate the ethics of communication in the cyber world.Keywords : communication ethics, cyber era.